Pengaruh Kepribadian Konsumen, Kualitas Produk, Dan Tampilan Produk Terhadap Keputusan Pembelian Honda Pcx Di Kota Batam - Raihan Muhammad Iqbal; Yunisa Oktavia (SCIENTIA JOURNAL, 2025)
This research study was conducted to evaluate the extent to which consumer personality, product quality, and product appearance influence the purchase decision of Honda PCX in Batam City. The research applies quantitative methods, utilizing 204 samples by applying Jacob's formula with purposive sampling techniques and the criteria that people have bought or owned a Honda PCX. Collection techniques through distributing questionnaires. Research checks using SPSS 26 include descriptive statistical tests, data quality tests, classical assumption tests, influence tests and hypothesis testing. The test results using multiple linear regression analysis state that consumer personality gets 9.1% associated with purchasing decisions. Product quality gets 36.5% associated with purchasing decisions. Product display gets a value of 15.8 associated with purchasing decisions. This shows the results of the variables of consumer personality, product quality, and product appearance simultaneously and importantly on purchasing decisions, by looking at R² 0.526, so that three of the variables listed obtained results 52.6% varied in relation to purchasing decisions. Referring to the results of the t test and F test, it confirms that consumer personality, product quality, and product appearance have a positive and significant influence on purchasing decisions for Honda PCX in Batam City.